Perdagangan Bebas Versus Proteksionisme - Tarmidi, Lepi T. (Jurnal Kebijakan Ekonomi, 2014)
For the past 20 years the world has seen a proliferation of Regional Free Trade Agreements. Some Indonesian economists are criticizing the negative effects of this “neo-liberal” thinking, instead they promote measures of protection to defend domestic industries. Every citizen must bea patriotand a nationalist, and not be a servant of great foreign economic powers. However, the greater majority of economists are for the idea of free trade, since it can bring prosperity to the people through the gains from trade. These economists are also nationalists. However, the controversy between free trade and protectionism has a long history, since the time of Mercantilism and Adam Smith. The author of this paper found out that the origin of this controversy is the misunderstanding of the term “free trade”. In practice “free trade” means liberalizing up to a certain point, because in each free trade agreement there are provisions about trade defence mechanism. There is only one example of real free trade, where there are no economic borders between countries, where there is an economic and monetary union (Euro), and that is the European Union.The paper concludes with chapter on Indonesia.